IMPLEMENTASI PLAN-DO-CHECK-ACT (PDCA) BERBASIS KEY PERFORMANCE INDICATORS (KPI): STUDI KASUS DI SMP-SMA INTEGRAL AR-ROHMAH DAU MALANG - Poppy Rachman (JURNAL AL-TANZIM, 2020)
This research is to analyze the process of development of quality management by using the cycled approach of PDCA (Plan-Do-Check-Act) based on KPI (Key Performance Indicators). This research was conducted at SMP-SMA Integral Ar-Rohmah "Boarding School" Dau Malang by using descriptive qualitative methods. The object of this research is around 449 students at SMP-SMA Integral Ar-Rohmah Dau Malang. The research period is the even semester of the 2018/2019 school year. The results of this study can be concluded that; Planning (Plan), produces three KPI formulation products, namely; a) KPI monitoring; b) KPI filling formula; and c) KPI report card. Implementation (Do), by requiring all students to participate in filling the KPI monitoring form and activeness of the musyrif room in assisting the filling of KPI. Evaluation (Check) that has been carried out is by means of a random check (random) conducted by the room meeting from the results of filling KPI monitoring. The follow up (Act) is to publish KPI report cards.